Control of hepatic gluconeogenesis by Argonaute2 - Xin Yan; Zhen Wang; Christopher A. Bishop; Karolin Weitkunat; Xiao Feng; Marcel Tarbier; Jiankai Luo; Marc R. Friedländer; Ralph Burkhardt; Susanne Klaus; Thomas E. Willnow; Matthew N. Poy (Elsevier, 2018)
Objective: The liver performs a central role in regulating energy homeostasis by increasing glucose output during fasting. Recent studies on Argonaute2 (Ago2), a key RNA-binding protein mediating the microRNA pathway, have illustrated its role in adaptive mechanisms according to changes in metabolic demand. Here we sought to characterize the functional role of Ago2 in the liver in the maintenance of systemic glucose homeostasis. Methods: We first analyzed Ago2 expression in mouse primary hepatocyte cultures after modulating extracellular glucose concentrations and in the presence of activators or inhibitors of glucokinase activity. We then characterized a conditional loss-of-function mouse model of Ago2 in liver for alterations in systemic energy metabolism. Results: Here we show that Ago2 expression in liver is directly correlated to extracellular glucose concentrations and that modulating glucokinase activity is adequate to affect hepatic Ago2 levels. Conditional deletion of Ago2 in liver resulted in decreased fasting glucose levels in addition to reducing hepatic glucose production. Moreover, loss of Ago2 promoted hepatic expression of AMP-activated protein kinase α1 (AMPKα1) by de-repressing its targeting by miR-148a, an abundant microRNA in the liver. Deletion of Ago2 from hyperglycemic, obese, and insulin-resistant Lepob/ob mice reduced both random and fasted blood glucose levels and body weight and improved insulin sensitivity. Conclusions: These data illustrate a central role for Ago2 in the adaptive response of the liver to fasting. Ago2 mediates the suppression of AMPKα1 by miR-148a, thereby identifying a regulatory link between non-coding RNAs and a key stress regulator in the hepatocyte. Keywords: RNA-binding proteins, Energy homeostasis, Glucose metabolism, Metabolic stress, microRNAs, Cellular adaptation